2022
DOI: 10.1097/ede.0000000000001553
|View full text |Cite
|
Sign up to set email alerts
|

Community Mitigation Strategies, Mobility, and COVID-19 Incidence Across Three Waves in the United States in 2020

Abstract: Background: Summarizing the impact of community-based mitigation strategies and mobility on COVID-19 infections throughout the pandemic is critical for informing responses and future infectious disease outbreaks. Here, we employed time-series analyses to empirically investigate the relationships between mitigation strategies and mobility on COVID-19 incident cases across US states during the first three waves of infections. Methods: We linked data on daily COVID-19 incidence by US state from March to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…TB treatment completion appeared consistent with the pre–COVID-19 era in which ≈75% of patients completed TB treatment within 12 months ( 10 ). As we previously described, the proportion of deaths among TB patients with COVID-19 was higher than for TB patients in the recent pre-pandemic period ( 5 ).…”
Section: Discussionsupporting
confidence: 61%
“…TB treatment completion appeared consistent with the pre–COVID-19 era in which ≈75% of patients completed TB treatment within 12 months ( 10 ). As we previously described, the proportion of deaths among TB patients with COVID-19 was higher than for TB patients in the recent pre-pandemic period ( 5 ).…”
Section: Discussionsupporting
confidence: 61%
“…Insights from previous literature indicated that travel restrictions, social distancing, and mask-wearing reduced the spread of COVID-19 (Kwon et al (2021), Wellenius et al , (2021) Ledesma et al (2022)) and that mask-wearing mitigated social-distancing efforts, thus, mitigating the reduction in the spread of COVID-19 (Liebst et al 2022). Since many protesters in Leipzig and Berlin did not comply with such mitigation strategies, we expect that these protests increased the spread of COVID-19 in these locations.…”
Section: Insights From Previous Literaturementioning
confidence: 98%